Google Android after Microsoft: Some Thoughts on the Proceedings Brought against Google for Abuse of a Dominant Position. (Cadernos de Dereito Actual, 2016)
In April 2015 the European Commission opened an antitrust proceedings against Google with regard to its business practices related to Android, the famous smarthpone and tablet operating system. According to the Commission, Google has abused of its dominant position in that it has allegedly required or incentivised smartphone and tablet manufacturers to exclusively pre-install Google’s own applications or services, prevented smartphone and tablet manufacturers from developing and marketing modified and potentially competing versions of Android, tied or bundled certain Google applications and services distributed on Android devices with other Google applications, services, and/or application programming interfaces of Google. The purpose of the article is to find a solution to the case in light of the judgment passed by the Court of First Instance of the European Union in Microsoft and show that Google's business practice does not amount to a violation of competition rules in that it protects both consumers and free competition.